The Development of QR-Code Preschooler Dismissal Management System using Laravel Framework - Syafiqah, Amira; Nur Ariffin Mohd Zin (Applied Information Technology And Computer Science, 2025)
In the context of modern educational challenges, institutions like Alkauthar Eduqids face issues with manual preschool dismissal systems, leading to inefficiencies and safety concerns. This study introduces the QR-Code Preschooler Dismissal Management System, designed to revolutionize these outdated methods by integrating web-based and mobile platforms. Through insights from the Alkauthar Eduqids case study, it’s evident that a single teacher and assistant overseeing numerous preschoolers using manual processes can result in logistical delays and safety risks. The research outlines structured objectives focused on system design, technology integration, and testing, with a specific emphasis on deployment at Alkauthar Eduqids and its broader relevance to similar settings. Anticipated outcomes emphasize improved operational efficiency and enhanced safety measures through features like QR-Code functionalities, supporting a more streamlined and secure dismissal experience. In summary, this investigation underscores the need for technological innovation in preschool dismissal systems, aiming to address critical safety and efficiency challenges prevalent in today’s educational environments.